(untitled) (Translation: The University of Toledo Journal of Medical Sciences, 2026)
Schizophrenia is a complex neuropsychiatric disorder with significant sex differences in onset, symptoms, and outcomes, suggesting that biological sex may influence disease mechanisms. However, molecular differences between males and females with schizophrenia remain poorly defined. This study examined sex-specific transcriptional alterations in the dorsolateral prefrontal cortex (DLPFC) of individuals with schizophrenia using publicly available RNA-sequencing data (GSE144136). Differential gene expression (DGE) analyses were performed separately for male and female cohorts, followed by gene set enrichment analysis (GSEA), leading-edge (LE) gene analysis, and perturbagen signature matching using the Library of Integrated Network-Based Cellular Signatures (iLINCS). No genes reached significance after correction, but unadjusted analyses revealed marked sex differences. Using the uncorrected analysis, Males exhibited over 2,000 differentially expressed genes distributed evenly between up- and downregulation, whereas females showed a smaller set of differentially expressed genes that were skewed towards upregulation. Pathway-level analyses showed that males displayed upregulation of metabolic pathways and downregulation of synaptic transport processes, while females exhibited upregulation of immune pathways alongside downregulation of vesicle organization and phosphoinositide metabolism. LE gene analysis supported the pathway changes. iLINCS analysis further highlighted sex-specific drug candidates whose expression profiles were discordant schizophrenia-associated signatures. FDA approved medications with high discordance included JAK2/mTOR pathway inhibitors and metabolic regulators in males, and immune or hormonal modulators in females. Taken together, these results reveal divergent molecular signatures that may underlie sex differences in schizophrenia pathophysiology. The identification of candidate drugs with discordant transcriptomic effects suggests potential therapeutic avenues and emphasizes the importance of sex stratified approaches in schizophrenia research.